Rationale of “Potency Test” as Performed on Alleged Accused of Sexual Offences in Age Old Forensic Practice- A Study - Sayak Sovan Dutta; Sandip Mukhopadhyay; Joydeep Khan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Following the amendment in Sec 375 IPC as per Criminal Law Amendment Act 2013, potencyis not at all essential to commit rape and so even an impotent man can rape a woman. Even after the change indefinition of rape and laws related to it in 2013, still the same age old question of potency is repeating in everyrequisition seeking medical examination of alleged accused of sexual offence. Investigating police officersask for potency test of the alleged accused persons irrespective of the type of sex offence committed by thepersons. MoreoverMedical examination report of the alleged accused is often labelled as the ‘‘POTENCYTEST REPORT” in the Court of Law disregarding all other findings. Method: Diagnosis of impotence isa multi-disciplinary approach. The aim of the study is to discuss the rationale of potency test in relation tosexual assault cases in light of CLAA (2013) and current practice followed in many Institutions.76 Allegedaccused of various sexual offence cases are studied here concerning the history of sexual offence, selfclaim of potency and duration between alleged incident and medicolegal examination. Conclusion: There isabsolutely no necessity of potency test if there is no history of peno-vaginal intercourse and if the accusedis not claiming himself to be impotent. Integrated approach between doctors and law enforcing agencies isessential to channelize the investigation in a more scientific way.